Prevalence of lingua plicata: A cross sectional study - Jacob, Lisa Elizabeth; Varghese, Stephy; Thomas, Jerin; Mathew, Anju; PM, Omal; John, Saumya (Journal of Oral Diagnosis, 2019)
Introduction: Fissured tongue is a common malformation characterized by deep grooves or fissures in the dorsum of the tongue. Fissured tongue is considered to be a variant of normal tongue architecture and is a totally benign condition. Objective: The aim of this present study is to examine the prevalence of fissured tongue, the most commonly occurring type of fissure and the association between the occurrence of fissured tongue with age, gender and, systemic conditions among the Kerala population who visited the dental OP in Pushpagiri College of Dental Sciences, Thiruvalla. Material and methods: A total of 500 patients consisting of 250 males and 250 females between the ages of 0-80 years were included in the study. The patients were divided into 4 age groups as 0-20 years, 20-40 years, 41-60 years and 61-80 years. The tongue was examined for the presence or absence of fissures, type of fissures and associated symptoms. The obtained data was subjected to statistical analysis using T test and ANOVA test with p value < 0.05 as statistically significant. Results: From a sample of 500, a total of 143 patients (prevalence rate of 28.6%) were found to have fissured tongue. The prevalence of fissured tongue was found to be significantly higher among males and was found to be more prevalent in the age group ranging from 41-60 years. A total of 103 patients had median fissures, 25 had lateral fissures and 30 had a combination of median and lateral fissures. Diabetes and hypertension were the most commonly observed systemic illness. Conclusion: Dentists and other oral health care workers need to be aware of the prevalence and management of patients with fissured tongue. As it’s a benign condition, fissured tongue requires no specific treatment.